Respuesta :

Answer:

(2x + 1)(3x - 2)

Step-by-step explanation:

f(x) = 6x² - x - 2

consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 6 × - 2 = - 12 and sum = - 1

the factors are + 3 and - 4

use these factors to split the x- term

6x² + 3x - 4x - 2 ( factor the first/second and third/fourth terms )

= 3x(2x + 1) - 2(2x + 1) ← factor out (2x + 1) from each term

= (2x + 1)(3x - 2) , then

f(x) = (2x + 1)(3x - 2) ← in factored form

ACCESS MORE